Hydrotreating catalysts, processes for their preparation and use
Patent Information
- Application Number
- CN202510416655.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-03
- Publication Date
- 2026-10-16
AI Technical Summary
[0010]本发明的主要目的在于提供一种加氢处理催化剂及其制备方法与应用,以克服现有技术加氢处理催化剂活性较弱、成本较高、或者用于油浆加氢脱硫时芳烃损失较大等缺陷
[0027] This invention utilizes pseudoboehmite with specific colloidal indices and pore volumes to prepare a large number of hydrotreating catalysts with pore structures of 15nm-30nm without the addition of acidic colloidal solvents and pore-expanding agents. The catalyst of this invention has a higher proportion of macropores, which facilitates the reaction and transformation of asphaltenes and colloidal macromolecules in the oil slurry within the catalyst pores, thereby improving the desulfurization rate and asphaltenes conversion capacity of the oil slurry.
Smart Images

Figure BDA0005344125000000071 
Figure BDA0005344125000000072 
Figure BDA0005344125000000101
Abstract
Description
Technical Field
[0001] This invention relates to the field of catalyst technology, and more particularly to hydrotreating catalysts and their preparation methods, as well as the application of hydrotreating catalysts in oil slurry hydrodesulfurization. Background Technology
[0002] Ultra-high power graphite electrodes are used in electric arc furnace steelmaking, which can reduce carbon emissions by 60% compared to blast furnace steelmaking. High-quality needle coke is a key raw material for ultra-high power graphite electrodes.
[0003] Catalytic cracking slurry is a rich byproduct of catalytic cracking (FCC), containing a large amount of 2-5 ring aromatics, and after catalytic cracking, almost all of them are short-chain aromatics. Low-sulfur catalytic cracking slurry can serve as an excellent feedstock for needle coke production. However, currently, there is a shortage of high-quality low-sulfur slurry suitable for needle coke production, necessitating the full utilization of medium- and high-sulfur slurry. However, medium- and high-sulfur slurry contains a large amount of sulfur, nitrogen, oxygen, and other heteroatoms, as well as asphaltene. When the sulfur content of needle coke is high (>0.8 wt%), it will cause irreversible volume expansion during graphitization, leading to the formation of microcracks and reducing electrode quality. Oil-based needle coke feedstock requires a sulfur content <0.5 wt%, ash content ≤100 mg / kg, asphaltene ≤2 wt%, and aromatic content 35-50 wt%. Therefore, to fully utilize existing medium- and high-sulfur catalytic cracking slurry, it needs to undergo hydrogenation pretreatment.
[0004] Pretreatment of medium- and high-sulfur catalytic slurry mainly involves slurry deconsolidation and refining processes. Filtration followed by furfural extraction or supercritical fluid extraction is used to adjust the slurry composition. Extensive research has been conducted both domestically and internationally on slurry refining, with hydrorefining being the primary process to reduce the content of impurities such as sulfur and nitrogen. For selective hydrodesulfurization of slurry, catalyst performance is crucial. The pore structure of the catalyst support (specific surface area, pore volume, and pore size distribution) significantly impacts not only the dispersion of active components but also directly affects diffusion and mass transfer during the reaction. Pore size and pore shape influence the internal diffusion rate of reactants and products. Most metallic and sulfur impurities in the slurry reside in gums and asphaltenes, which are the components with the largest molecular weight and most complex structure, exhibiting significant diffusion resistance and a tendency to cause pore blockage (leading to catalyst deactivation). Therefore, catalyst pore volume is particularly important; a large pore size is necessary to facilitate the passage of large impurity molecules and their reaction within the catalyst channels, while maintaining a large specific surface area is beneficial for desulfurization activity. Although catalytic cracking slurry is a byproduct of catalytic cracking reaction with smaller molecular size and shorter side chains, resulting in less steric hindrance, it is still necessary to directionally increase the content of 15-20nm and 20-30nm pores to promote the adsorption and desorption reactions of macromolecular sulfides and asphaltenes in the catalyst pores for conversion.
[0005] CN108102711B provides a combined process for producing needle coke. The method involves feeding feedstock oil into a catalytic cracking unit. After reaction and separation, the resulting catalytic slurry is mixed with hydrogen and then fed into a fluidized bed reactor. The liquid heavy components obtained from the fluidized bed reactor effluent are separated and fed into a coking unit. The oil and gas generated during coking are separated to obtain gas, coking gasoline, coking diesel, and coking wax oil. After the reaction cycle, the resulting needle coke is deposited in the coking unit. In this method, the catalytic section of the fluidized bed reactor is filled with a hydrotreating catalyst. The specific surface area of the catalyst in this invention is 120 m². 2 / g~300m 2 / g, preferably 160m 2 / g~280m 2 / g; pore volume is 0.2mL / g to 0.8mL / g, preferably 0.4mL / g to 0.6mL / g; average pore size is 8nm to 13nm, preferably 9nm to 11nm and the following pore size distribution: pores with diameters of 4nm to 10nm account for 70% to 80% of the total pore volume, and pores with diameters of 15nm account for 5% to 10% of the total pore volume. This invention has a complex process, uses catalysts with small pore volumes and sizes, which is not conducive to the diffusion of macromolecules such as asphaltenes, and requires relatively harsh hydrogenation process conditions. Although it can remove sulfur impurities from the catalytic slurry, some aromatics are lost.
[0006] CN106622314 A discloses a highly active hydrorefining catalyst and its preparation method. The method uses water as a solvent to prepare a slurry containing silicon-phosphorus alumina. A boron-containing compound, a Group VIB metal compound, and a Group VIII metal compound are added to the slurry. After filtration, a filter cake and a filtrate are obtained. The filtrate is mixed with SB powder and a peptizing solvent to obtain a binder. The binder and the filter cake are sequentially rolled, shaped, dried, and calcined to obtain the hydrorefining catalyst. This catalyst has a small pore volume and a rapid deactivation rate.
[0007] CN1417300A discloses a hydrogenation catalyst and its preparation method. The preparation method of the catalyst includes impregnating a macroporous alumina support with a solution containing Group VIB and Group VIII metal compounds. The preparation method of the alumina support includes extruding a mixture of boehmite, acid, water and extrusion aid, rapidly drying the formed article at 90-300°C within 35 minutes, and calcining it at 600-800°C in a water vapor atmosphere for at least 0.5 hours. The resulting alumina support has a pore distribution in which pores with a diameter of 10-20 nm account for 70-90% of the total pore volume.
[0008] CN1103009A discloses a method for preparing a catalyst support for the hydrodemetallization of heavy oil. This method involves using two aluminum hydroxide precursors with different pore sizes, adding carbon black and a surfactant as pore expanders, and then mixing, molding, drying, and calcining to form a dual-porous alumina support. This method has stringent requirements for the alumina precursor raw materials, requires the addition of a large amount of surfactant as a pore expander, and is therefore costly.
[0009] As can be seen from the above, further research is needed in this field on hydrotreating catalysts to prepare hydrotreating catalysts with high hydrotreating activity and low aromatic loss at low cost. Summary of the Invention
[0010] The main objective of this invention is to provide a hydrotreating catalyst, its preparation method, and its application, in order to overcome the shortcomings of existing hydrotreating catalysts, such as weak activity, high cost, or significant aromatic loss when used for hydrodesulfurization of oil slurry.
[0011] To achieve the above objectives, the present invention provides a hydrotreating catalyst comprising a support and an active component, wherein the active component is supported on the support, the support being formed of boehmite, a binder, and water, wherein the boehmite has a colloidal index ≥20% and a pore volume ≥1.00 ml / g; and the active component comprises Group VIB and / or Group VIII metals.
[0012] The hydrotreating catalyst of the present invention, wherein the pseudoboehmite has a specific surface area ≥330 m². 2 / g, with a colloidal index of 25% to 35%; and / or, the pore volume of the hydrogenated catalyst is 0.55-0.98 ml / g, with pores of 15nm-20nm accounting for 35%-55% of the total pore volume, and pores of 20-30nm accounting for 20%-40% of the total pore volume.
[0013] To achieve the above objectives, the present invention also provides a method for preparing a hydrogenation catalyst, comprising the following steps:
[0014] Step 1: Mix boehmite, binder and water to prepare catalyst support;
[0015] Step 2: Impregnate the catalyst support with the active component impregnation solution, dry, and calcine to obtain the hydrogenation-treated catalyst;
[0016] The pseudoboehmite has a colloidal index ≥20% and a pore volume ≥1.00 ml / g; the active component impregnation solution includes an active component precursor, which is a Group VIB metal compound and / or a Group VIII metal compound.
[0017] The method for preparing the hydrotreating catalyst of the present invention, wherein the specific surface area of the pseudoboehmite is ≥330 m². 2 / g, with a colloidal index of 25%–35%.
[0018] The method for preparing the hydrogenation catalyst of the present invention, wherein the binder is guar gum powder and / or starch, and the amount of binder added is 1% to 6% of the mass of alumina in the pseudoboehmite.
[0019] The method for preparing the hydrotreating catalyst according to the present invention includes an active component impregnation solution comprising an inorganic acid and a complexing agent, wherein the amount of inorganic acid added is 1% to 10% of the total mass of the hydrotreating catalyst, and the amount of complexing agent added is 1% to 15% of the total mass of the hydrotreating catalyst.
[0020] The method for preparing the hydrogenation catalyst of the present invention includes wherein the inorganic acid is at least one selected from phosphoric acid, nitric acid, and hydrochloric acid; and the complexing agent is an amino acid compound.
[0021] The method for preparing the hydrogenation catalyst of the present invention, wherein the amino acid compound is one or more of arginine, histidine, and lysine.
[0022] The method for preparing the hydrogenation catalyst according to the present invention, wherein the Group VIB metal compound is at least one of a Mo compound and a W compound; and the Group VIII metal compound is at least one of a Ni compound and a Co compound;
[0023] After mixing in step 1, the process also includes drying and calcination. The drying temperature is 100-200℃, the calcination temperature is 600-900℃, and the calcination time is 0.5-6 hours.
[0024] Step 2: The drying temperature is 100-200℃, the calcination temperature is 300-500℃, and the calcination time is 0.5-6 hours.
[0025] To achieve the above objectives, the present invention also provides the application of the hydrotreating catalyst obtained by the above preparation method in the hydrodesulfurization treatment of oil slurry.
[0026] The beneficial effects of this invention are:
[0027] This invention utilizes pseudoboehmite with specific colloidal indices and pore volumes to prepare a large number of hydrotreating catalysts with pore structures of 15nm-30nm without the addition of acidic colloidal solvents and pore-expanding agents. The catalyst of this invention has a higher proportion of macropores, which facilitates the reaction and transformation of asphaltenes and colloidal macromolecules in the oil slurry within the catalyst pores, thereby improving the desulfurization rate and asphaltenes conversion capacity of the oil slurry. Detailed Implementation
[0028] The technical solution of the present invention will be described in detail below. The following embodiments are implemented under the premise of the technical solution of the present invention and a detailed implementation process is given. However, the protection scope of the present invention is not limited to the following embodiments. Structures or experimental methods that do not specify specific conditions in the following embodiments are generally performed under conventional conditions.
[0029] This invention provides a hydrotreating catalyst, comprising a support and an active component, wherein the active component is supported on the support, which is formed of boehmite, a binder and water, wherein the boehmite has a colloidal index ≥20% and a pore volume ≥1.00 ml / g; the active component comprises Group VIB and / or Group VIII metals.
[0030] This invention utilizes boehmite with specific colloidal indices and pore volumes, forming a carrier solely from boehmite, a binder, and water, without the need for acidic colloidal solvents or pore-expanding agents, to prepare a large number of hydrotreating catalysts with 15nm-30nm pore structures. The catalyst of this invention has a high proportion of macropores, which, when used in the hydrodesulfurization of catalytic cracking slurry, facilitates the reaction and transformation of asphaltenes and colloidal macromolecules within the catalyst pores, thereby improving the desulfurization rate and asphaltenes conversion capacity of the slurry, while also reducing catalyst cost.
[0031] In one embodiment, the specific surface area of the pseudoboehmite of the present invention is ≥330 m². 2 / g, pore volume ≥1.00ml / g, preferably ≥1.20ml / g, and colloidal index of 20% to 40%, preferably 25% to 35%.
[0032] In one embodiment, the binder of the present invention is guar gum powder, and the amount of binder added is 1% to 6% of the mass of alumina in the pseudoboehmite. The present invention does not particularly limit the amount of water added, and can be adjusted as needed.
[0033] In one embodiment, the hydrogenation catalyst of the present invention comprises at least one Group VIB metal selected from Mo and W, and at least one Group VIII metal selected from Ni and Co. The Group VIB metal, as an oxide, accounts for 8 wt% to 20 wt% of the total catalyst mass, and the Group VIII metal, as an oxide, accounts for 2 wt% to 5 wt% of the total catalyst mass.
[0034] The present invention also provides a method for preparing a hydrotreating catalyst, which can be the above-mentioned hydrotreating catalyst, comprising the following steps:
[0035] Step 1: Mix boehmite, binder and water to prepare catalyst support;
[0036] Step 2: Impregnate the catalyst support with the active component impregnation solution, dry, and calcine to obtain the hydrogenation-treated catalyst;
[0037] Among them, the gel solubility index of pseudoboehmite is ≥20%, and the pore volume is ≥1.00ml / g; the active component impregnation solution includes the active component precursor, which is a Group VIB metal compound and / or a Group VIII metal compound.
[0038] This invention utilizes boehmite with specific colloidal indices and pore volumes, forming a support solely from boehmite, a binder, and water, without the need for acidic colloidal solvents or pore-expanding agents, to prepare a large number of hydrotreating catalysts with pore structures of 15nm-30nm. The catalysts prepared by this method have a high proportion of macropores, which, when used in the hydrodesulfurization of catalytic cracking slurry, facilitates the reaction and transformation of asphaltenes and gum macromolecules within the catalyst pores, thereby improving the desulfurization rate and asphaltenes conversion capacity of the slurry, while also reducing catalyst cost.
[0039] In one embodiment, the specific surface area of the pseudoboehmite of the present invention is ≥330 m². 2 / g, pore volume ≥1.00ml / g, preferably ≥1.20ml / g, and colloidal index of 25%~35%.
[0040] In one embodiment, the binder of the present invention is guar gum powder and / or starch, and the amount of binder added is 1% to 6% of the mass of alumina in the boehmite, preferably 2% to 4%. The present invention does not particularly limit the amount of water added, and can be adjusted as needed.
[0041] After mixing in step 1 of this invention, the process may also include drying and calcination steps. The drying temperature is 100-200℃, the calcination temperature is 600-900℃, preferably 700-850℃, and the calcination time is 0.5-6 hours.
[0042] The present invention does not particularly limit the shape of the catalyst support, and it can be changed as needed, such as cylindrical, clover-shaped, four-leaf clover-shaped, and spherical. In one embodiment, the mixing process in step 1 of the present invention is carried out using a screw extruder with an extrusion pressure of 15-50 MPa.
[0043] The present invention does not impose particular limitations on the impregnation method of the catalyst support in step 2, which involves impregnating the active component in the impregnation solution. For example, the catalyst support can be added to the active component impregnation solution for impregnation. In one embodiment, the active component impregnation solution further includes an inorganic acid and a complexing agent. The amount of inorganic acid added is 1% to 10% of the total mass of the hydrotreated catalyst, and the amount of complexing agent added can be 1% to 15% of the total mass of the hydrotreated catalyst, preferably 3% to 10%.
[0044] In one embodiment, the inorganic acid is one or more of phosphoric acid, nitric acid, and hydrochloric acid. The complexing agent is an amino acid compound, specifically one or more of arginine, histidine, and lysine. The addition of the amino acid complexing agent can improve the dispersion and acidity of the active metal, allowing the catalyst to retain tricyclic and tetracyclic aromatics when used for hydrotreating catalytic cracking slurry, thus avoiding the loss of aromatics during hydrotreating.
[0045] In this invention, the active component precursor is a Group VIB metal compound and / or a Group VIII metal compound. The Group VIB metal is at least one of Mo and W, and the Group VIII metal is at least one of Ni and Co. The Mo compound can be one or more of ammonium molybdate, sodium phosphomolybdate, ammonium phosphomolybdate, and molybdenum trioxide; the W compound can be one or more of W₂O₅, WO₃, and ammonium metatungstate; the Ni compound can be one or more of nickel nitrate, nickel acetate, and basic nickel carbonate; and the Co compound can be one or more of cobalt nitrate, cobalt acetate, and basic cobalt carbonate. Based on oxides, molybdenum and / or tungsten account for 8 wt% to 20 wt% of the total catalyst mass, and nickel and / or cobalt account for 2 wt% to 5 wt% of the total catalyst mass.
[0046] After impregnation in step 2, the catalyst is dried and calcined to obtain the hydrotreated catalyst. The drying temperature can be 100-200℃, the calcination temperature can be 300-500℃, preferably 350-450℃, and the calcination time can be 0.5-6 hours.
[0047] The hydrotreating catalyst of this invention has a pore volume of 0.55-0.98 ml / g, with pores of 15 nm-20 nm accounting for 35%-55% of the total pore volume, and pores of 20-30 nm accounting for 20%-40% of the total pore volume. The hydrotreating catalyst prepared by the method of this invention can be used for hydrotreating slurry oil, such as catalytic cracking slurry oil. It can effectively remove sulfur from catalytic cracking slurry oil, promote the conversion of asphaltenes in catalytic cracking slurry oil, and retain tricyclic and tetracyclic aromatic hydrocarbons in the slurry oil.
[0048] This invention does not use acidic colloidal solvents and pore-expanding agents to prepare hydrotreating catalysts. The preparation process is simple, reducing the influence of acidic colloidal solvents on the catalyst pores and giving the catalyst a good pore structure. When the catalyst of this invention is used for slurry hydrotreating, it can catalyze the adsorption and removal of complex sulfur-containing compounds and asphaltenes in the slurry. While promoting the conversion and desulfurization of asphaltenes, it retains as many tricyclic and tetracyclic aromatic hydrocarbons as possible in the catalytic cracking slurry, providing high-quality feedstock for the production of high-quality needle coke.
[0049] The technical solution of the present invention will be further described in detail below through specific embodiments.
[0050] Determination of the gel solubility index of pseudoboehmite dry adhesive powder
[0051] Phobospore is dissolved in nitric acid of a certain concentration, and a colloid is formed by stirring. After standing and separating the liquid, the colloidal index is determined. The specific steps are as follows:
[0052] (1) Determine the aluminum oxide content in the sample:
[0053] Weigh approximately 1.5 grams of the sample, record it as m1, and place it in a crucible (crucible weight m0). Then, place it in a high-temperature furnace and heat it from room temperature to 800°C for 2 hours. Remove it, place it in a desiccator, cool it to room temperature, and weigh it quickly. Accurate to 0.0001 grams. Record the crucible and the sample after ignition as m2. The aluminum oxide content is calculated using the following formula:
[0054]
[0055] Where m1 is the weight of the sample before ignition, in g;
[0056] m2 is the weight of the sample and crucible after ignition, in grams;
[0057] m0 is the weight of the crucible, in grams.
[0058] (2) Analysis steps
[0059] Calculate the weight X grams of the sample containing 2.00 grams of aluminum oxide:
[0060]
[0061] In the formula, X is the weight of the sample containing 2.00 grams of aluminum oxide, in g;
[0062] Accurately weigh X grams of sample into a 150 ml crucible. Weigh (50-X) grams of water into the crucible using a beaker and pour it into the crucible. Begin magnetic stirring to prepare a 4% aluminum oxide solution. Measure 7.0 ml (V) of 4% (φ%) nitric acid using a graduated cylinder. 硝酸 V 水 =1:25), slowly add the nitric acid using a plastic dropper, starting the timer from the addition of nitric acid, and continue magnetic stirring for 15 minutes. Let stand for 24 hours, remove the upper suspension, dry, ignite at 800℃ for 2 hours, remove, place in a desiccator, cool to room temperature, and weigh the sample mass m3.
[0063] (3) Calculation of the gelation index
[0064] DI = (2.00 - m³) / 2.00
[0065] In the formula, DI is the gel solubility index, %;
[0066] m3 is the weight of aluminum oxide in the crucible after calcination, in grams.
[0067] Example 1
[0068] Weigh out 500g of pseudoboehmite dry adhesive powder (specific surface area 330m²). 2 (Metal content: / g, pore volume 1.21ml / g, colloidal index 25%), add 3.5g of guar gum powder, mix evenly, add purified water, knead and shape, extrude into clover-shaped particles with a particle size of 1.4-1.6mm on a front-extrusion single-screw extruder, extrusion pressure 15MPa, dry at 100℃ for 3 hours, calcine at 700℃ for 6 hours to prepare catalyst support; add 100ml of Mo-Ni-H3PO4 solution (catalyst contains 10wt% MoO3, 5wt% NiO) for impregnation, dry at 100℃ for 3 hours, calcine at 400℃ for 4 hours to obtain catalyst A1. The Mo-Ni-H3PO4 solution is prepared as follows: add 50g of molybdenum trioxide to 50ml of H3PO4 solution and stir until completely dissolved, then add 32g of basic nickel carbonate and stir until completely dissolved, then add 15g of arginine and stir until completely dissolved, then add water to 100ml. Catalyst properties are shown in Table 1.
[0069] Example 2
[0070] Weigh out 500g of pseudoboehmite dry adhesive powder (specific surface area 330m²). 2 (Metal content: / g, pore volume 1.20ml / g, colloidal index 35%), add 3.5g of guar gum powder, mix evenly, add purified water, knead and shape, extrude into clover-shaped particles with a particle size of 1.6mm on a front-extrusion single-screw extruder, extrusion pressure 40MPa, dry at 100℃ for 3 hours, calcine at 900℃ for 3 hours to prepare catalyst support; add 100ml of Mo-Ni-H3PO4 solution (catalyst contains 10wt% MoO3, 5wt% NiO) for impregnation, dry at 100℃ for 3 hours, calcine at 500℃ for 4 hours to obtain catalyst A2. The Mo-Ni-H3PO4 solution is prepared as follows: add 50g of molybdenum trioxide to 500ml of H3PO4 solution and stir until completely dissolved, then add 32g of basic nickel carbonate and stir until completely dissolved, then add 45g of histidine and stir until completely dissolved, then add water to 100ml. Catalyst properties are shown in Table 1.
[0071] Example 3
[0072] Weigh out 500g of pseudoboehmite dry adhesive powder (specific surface area 330m²). 2 / g, pore volume 1.25ml / g, colloidal index 30%), add 3.5g of guar gum powder, mix evenly, add purified water, knead and shape, extrude into clover-shaped particles with a particle size of 1.6mm on a front-extrusion single-screw extruder, extrusion pressure 40MPa, dry at 100℃ for 3 hours, calcine at 800℃ for 3 hours to prepare catalyst support; add 100ml of Mo-Ni-H3PO4 solution (catalyst contains 10wt% MoO3 and 5wt% NiO) for impregnation, dry at 100℃ for 3 hours, calcine at 450℃ for 4 hours, wherein the Mo-Ni-H3PO4 solution is prepared as follows: add 50g of molybdenum trioxide to 100ml of H3PO4 solution and stir until completely dissolved, add 32g of basic nickel carbonate and stir until completely dissolved, add 45g of lysine and stir until completely dissolved, and add water to make up to 500ml; the properties of the catalyst are shown in Table 1.
[0073] Example 4
[0074] Weigh out 500g of pseudoboehmite dry adhesive powder (specific surface area 330m²). 2 / g, pore volume 1.25ml / g, colloidal index 30%), add 3.5g of guar gum powder, mix evenly, add purified water, knead and shape, extrude into clover-shaped particles with a particle size of 1.6mm on a front-extrusion single-screw extruder, extrusion pressure 40MPa, dry at 100℃ for 3 hours, calcine at 800℃ for 3 hours to prepare catalyst support; add 100ml of Mo-Ni-H3PO4 solution (catalyst contains 10wt% MoO3 and 5wt% NiO) for impregnation, dry at 100℃ for 3 hours, calcine at 450℃ for 4 hours, wherein the Mo-Ni-H3PO4 solution is prepared as follows: add 50g of molybdenum trioxide to 100ml of H3PO4 solution and stir until completely dissolved, then add 32g of basic nickel carbonate and stir until completely dissolved, then add water to make up to 500ml; the properties of the catalyst are shown in Table 1.
[0075] Comparative Example 1
[0076] According to the method described in Chinese Patent CN106622314 A, 25g of molybdenum trioxide and 16g of basic nickel carbonate were added to a slurry containing silicon-phosphorus alumina. The mixture was filtered to obtain a filter cake and a filtrate. The filtrate was mixed with SB powder and a binder to obtain a binder. The binder and the filter cake were extruded together on a pre-extrusion single-screw extruder to form clover-shaped pellets with a diameter of 1.6mm. The pellets were dried at 120℃ for 3 hours and then calcined at 800℃ for 5 hours to obtain catalyst B1. The physical properties of the catalyst are shown in Table 1.
[0077] Comparative Example 2
[0078] According to the method described in Chinese Patent CN96120423A, 300g of pseudoboehmite was weighed, 18g of guar gum powder was added, and the mixture was stirred evenly. 60g of 4wt% ammonia solution was added to the aforementioned material and thoroughly mixed. Then, 152g of an 8wt% acetic acid aqueous solution was added to the above material and thoroughly mixed. The mixture was then extruded into a clover shape with a diameter of 1.6mm on a front-extrusion single-screw extruder, dried at 120℃ for 3 hours, and then calcined at 850℃ for 5 hours to prepare an alumina carrier. This carrier was then impregnated with 150ml of Mo-Ni-H3PO4 solution (containing 10wt% MoO3 and 5wt% NiO). The Mo-Ni-H3PO4 solution was prepared as follows: [The text abruptly ends here, so the translation stops as well.] After 25g of molybdenum trioxide was added to the H3PO4 solution and stirred until completely dissolved, 16g of basic nickel carbonate was added and stirred until completely dissolved. Water was then added to bring the volume to 150ml. After spray impregnation, excess solution was filtered off, dried at 120℃ for 3 hours, and then calcined at 500℃ for 4 hours to obtain catalyst B2. The physical properties of the catalyst are shown in Table 1.
[0079] Comparative Example 3
[0080] According to the method described in Chinese Patent CN1417300A, 300g of boehmite was weighed and mixed evenly with 3.9g of 65wt% nitric acid, 3g of guar gum powder and 120g of deionized water. The mixture was then extruded into a 1.6mm clover shape on an extruder. The substrate was dried by forced air at 110℃. After drying, the dried molded material was calcined at 750℃ with 100% steam for 5 hours to obtain the support. 150 ml of Mo-Ni-H3PO4 solution (containing 10 wt% MoO3 and 3.5 wt% NiO3) was added to the obtained support for impregnation. The Mo-Ni-H3PO4 solution was prepared as follows: 25 g of molybdenum trioxide was added to 100 ml of H3PO4 solution and stirred until completely dissolved. Then, 16 g of basic nickel carbonate was added and stirred until completely dissolved. Water was added to bring the volume to 150 ml. After impregnation, excess solution was filtered off, and the substrate was dried at 120℃ for 3 hours, followed by calcination at 500℃ for 4 hours to obtain catalyst B3. The catalyst properties are shown in Table 1.
[0081] Comparative Example 4
[0082] Weigh out 500g of pseudoboehmite dry adhesive powder (specific surface area 330m). 2(Metal content: / g, pore volume 1.20ml / g, colloidal index 12%), add 3.5g of guar gum powder, mix evenly, add purified water, knead and shape, extrude into clover-shaped particles with a particle size of 1.6mm on a front-extrusion single-screw extruder, extrusion pressure 40MPa, dry at 100℃ for 3 hours, calcine at 900℃ for 3 hours to prepare catalyst support; add 100ml of Mo-Ni-H3PO4 solution (catalyst contains 10wt% MoO3, 5wt% NiO) for impregnation, dry at 100℃ for 3 hours, calcine at 500℃ for 4 hours to obtain catalyst B4. The Mo-Ni-H3PO4 solution is prepared as follows: add 50g of molybdenum trioxide to 500ml of H3PO4 solution and stir until completely dissolved, then add 32g of basic nickel carbonate and stir until completely dissolved, then add 45g of histidine and stir until completely dissolved, then add water to 100ml. Catalyst properties are shown in Table 1.
[0083] Table 1 Catalyst Properties
[0084]
[0085] As shown in Table 1, compared with the comparative catalyst, the catalyst prepared by the method described in the present invention has a larger specific surface area and pore volume, and a significantly higher content of pores with pore sizes of 15-20 nm and 20-30 nm.
[0086] The activity and stability of the catalysts in the examples and comparative examples were evaluated. The evaluation conditions are shown in Table 2, and the evaluation results are shown in Table 3.
[0087] Table 2 Catalyst Evaluation Conditions
[0088]
[0089]
[0090] Table 3 Catalyst Evaluation Results
[0091] catalyst A1 A2 A3 A4 B1 B2 B3 B4 Sulfur content, wt% 0.38 0.35 0.36 0.39 0.40 0.39 0.41 0.40 Third Ring Road + Fourth Ring Road, wt% 45.2 46.3 46.0 44.3 41.5 42.3 41.9 42.6 Asphalt, wt% 2.1 1.9 2.1 2.3 2.9 2.9 2.7 2.5
[0092] As shown in Table 3, when the catalyst of the present invention is used for hydrotreating catalytic cracking slurry, it exhibits a high sulfur removal rate, low aromatic hydrocarbon loss, and high asphaltene conversion capacity.
[0093] Of course, the present invention may have other various embodiments. Without departing from the spirit and essence of the present invention, those skilled in the art can make various corresponding changes and modifications according to the present invention, but these corresponding changes and modifications should all fall within the protection scope of the claims of the present invention.
Claims
1. A hydrogenation catalyst, characterized in that, The product includes a carrier and an active component, wherein the active component is loaded on the carrier, which is formed from boehmite, a binder and water, wherein the boehmite has a colloidal index ≥20% and a pore volume ≥1.00 ml / g; and the active component includes Group VIB and / or Group VIII metals.
2. The hydrotreating catalyst according to claim 1, characterized in that, The specific surface area of the pseudoboehmite is ≥330 m². 2 / g, with a colloidal index of 25% to 35%; and / or, the pore volume of the hydrogenated catalyst is 0.55-0.98 ml / g, with pores of 15nm-20nm accounting for 35%-55% of the total pore volume, and pores of 20-30nm accounting for 20%-40% of the total pore volume.
3. A method for preparing a hydrogenation catalyst, characterized in that, Includes the following steps: Step 1: Mix boehmite, binder and water to prepare catalyst support; Step 2: Impregnate the catalyst support with the active component impregnation solution, dry, and calcine to obtain the hydrogenation-treated catalyst; The pseudoboehmite has a colloidal index ≥20% and a pore volume ≥1.00 ml / g; the active component impregnation solution includes an active component precursor, which is a Group VIB metal compound and / or a Group VIII metal compound.
4. The method for preparing the hydrogenation catalyst according to claim 3, characterized in that, The specific surface area of the pseudoboehmite is ≥330 m². 2 / g, with a colloidal index of 25%–35%.
5. The method for preparing the hydrogenation catalyst according to claim 3, characterized in that, The binder is guar gum powder and / or starch, and the amount of binder added is 1% to 6% of the mass of alumina in the pseudoboehmite.
6. The method for preparing the hydrotreating catalyst according to claim 3, characterized in that, The active component impregnation solution includes an inorganic acid and a complexing agent. The amount of inorganic acid added is 1% to 10% of the total mass of the hydrogenation catalyst, and the amount of complexing agent added is 1% to 15% of the total mass of the hydrogenation catalyst.
7. The method for preparing the hydrogenation catalyst according to claim 6, characterized in that, The inorganic acid is at least one of phosphoric acid, nitric acid, and hydrochloric acid; the complexing agent is an amino acid compound.
8. The method for preparing the hydrogenation catalyst according to claim 7, characterized in that, The amino acid compound is one or more of arginine, histidine, and lysine.
9. The method for preparing the hydrogenation catalyst according to claim 3, characterized in that, The group VIB metal compound is at least one of Mo and W compounds; the group VIII metal compound is at least one of Ni and Co compounds. After mixing in step 1, the process also includes drying and calcination. The drying temperature is 100-200℃, the calcination temperature is 600-900℃, and the calcination time is 0.5-6 hours. Step 2: The drying temperature is 100-200℃, the calcination temperature is 300-500℃, and the calcination time is 0.5-6 hours.
10. The application of the hydrotreating catalyst obtained by the preparation method according to any one of claims 3-9 in the hydrodesulfurization treatment of oil slurry.
Citation Information
Patent Citations
Catalyzer for hydrotreating residuum and its prepn. method
CN1053458C
High-activity hydrofining catalyst and preparation method thereof
CN106622314A
A combined process for producing needle coke
CN108102711B
Preparing method for aluminium oxide carrier with double-hole
CN1103009A
Hydrogenating and demetalization catalyst and its prepn
CN1417300A